Sliding mode controller design for a flying quadrotor with simplified action planner - Mohamed, H.A.F.; Yang, S.S.; Moghavvemi, M. (2009)
This paper presents the design of a set of sliding mode controllers for a quadrotor vertical take-off and landing (VTOL) unmanned air vehicle. To facilitate the design process of this under-actuated system, this paper proposes the use of a simple yet effective method to plan the action of each variable controller in the system and hence enhance the performance of the quadrotor. To stabilize the overall system, each sliding mode controller is designed based on the Lyapunov stability theory. Various simulations of the model show that the proposed control method stabilizes the quadrotor and achieves good tracking performance.